Implementasi Algoritma Prediction By Partial Matching (Ppm) Pada Kompresi File Teks Terenkripsi Elgamal - Relina Hutagalung (STMIK Budi Darma, 2018)
Computer security is a branch of technology known as information security applied to computers. The goal of computer security is to protect information against information theft. The application of computer security is an effort made to secure performance and computerized processes so that they are not used, modified, interrupted and disturbed by unauthorized parties. While data compression is one of the important aspects of the development of information technology. Compression is converting data into forms that require fewer bits, usually done so that data can be stored or sent more efficiently. The speed in the process of sending information is something that is highly expected by using existing technology and will be hampered if the file containing the information has a large size. Not only kecepan, security factors are very important things in the exchange of information. This is because many irresponsible parties want to steal information and can be misused by that party. The compression technique using the Prediction by Partial Matching algorithm can overcome large file sizes because by using the algorithm the file size can be minimized. Whereas to improve the security of confidential information, then encoding text files using the ElGamal algorithm which has a level of security that is quite strong because of the difficulty in calculating discrete logarithms to solve them. The final result is a text file that has been encoded and has a smaller size.